2006
DOI: 10.1136/bmj.39048.407928.be
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment effects between animal experiments and clinical trials: systematic review

Abstract: Objective To examine concordance between treatment effects in animal experiments and clinical trials. Study design Systematic review. Data sources Medline, Embase, SIGLE, NTIS, Science Citation Index, CAB, BIOSIS. Study selection Animal studies for interventions with unambiguous evidence of a treatment effect (benefit or harm) in clinical trials: head injury, antifibrinolytics in haemorrhage, thrombolysis in acute ischaemic stroke, tirilazad in acute ischaemic stroke, antenatal corticosteroids to prevent neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
544
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 680 publications
(557 citation statements)
references
References 26 publications
9
544
2
2
Order By: Relevance
“…Major discrepancies between drug effects in animal models and in human trials have recently been pointed out, which may be due to design of the models, assessment tools for determination of drug efficacy, and timing of drug application (Perel et al, 2007). These facts have to be taken into consideration, especially for long term drug intervention studies.…”
Section: Resultsmentioning
confidence: 99%
“…Major discrepancies between drug effects in animal models and in human trials have recently been pointed out, which may be due to design of the models, assessment tools for determination of drug efficacy, and timing of drug application (Perel et al, 2007). These facts have to be taken into consideration, especially for long term drug intervention studies.…”
Section: Resultsmentioning
confidence: 99%
“…This compares favorably to the 24% reduction reported in a meta-analysis of preclinical data for tissue plasminogen activator. 2 In contrast to other similar meta-analyses, 3,4 in which the efficacy detected in individual studies declined with higher ''quality scores,'' the reported efficacy of IL-1RA increases when more of the 10 ''quality items'' are reported in the study's methods. We welcome the authors' thorough analysis of much of the current knowledge regarding the efficacy of IL-1RA in animal models of stroke, and agree that there is room for improvements in the conduct of preclinical studies in stroke.…”
Section: To the Editormentioning
confidence: 84%
“…It is well known that discrepancies exist between animal and human data and that a drug that is active in the animal may be useless in the human (Perel et al, 2007). Such an occurrence is often due to inappropriate translation of the drug dose from one animal species to another.…”
Section: Tablementioning
confidence: 99%